2018
DOI: 10.3390/sports7010004
|View full text |Cite
|
Sign up to set email alerts
|

Preseason Y Balance Test Scores are not Associated with Noncontact Time-Loss Lower Quadrant Injury in Male Collegiate Basketball Players

Abstract: The Y-Balance Test-Lower Quarter has shown promise as a screening tool for identifying athletes at risk of injury. Subsequent studies, utilizing heterogeneous populations or different operational definitions of injury, have presented equivocal findings. Therefore, studies evaluating the efficacy of the Y-Balance Test to discriminate injury risk in a homogeneous population is warranted. One-hundred sixty-nine male (mean age 19.9 ± 1.5 y) collegiate basketball players were recruited during 2 consecutive seasons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…While earlier studies on American football [11] and soccer [17] reported significant associations between YBT-LQ scores and injury, these findings have not been validated in subsequent samples. Our findings are consistent with recent papers that have concluded that the YBT-LQ may have limited utility in isolation as a screening test for non-contact LQ injury [29,31,32]. In 2017, Wright et al [32] noted that YBT-LQ composite scores or asymmetries were not predictive of lower extremity injury in 189 collegiate athletes from six sports.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…While earlier studies on American football [11] and soccer [17] reported significant associations between YBT-LQ scores and injury, these findings have not been validated in subsequent samples. Our findings are consistent with recent papers that have concluded that the YBT-LQ may have limited utility in isolation as a screening test for non-contact LQ injury [29,31,32]. In 2017, Wright et al [32] noted that YBT-LQ composite scores or asymmetries were not predictive of lower extremity injury in 189 collegiate athletes from six sports.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, Lai et al [29] determined that cutoff scores of 2, 3, and 9 cm for asymmetry in anterior, posterolateral, and posteromedial reach, respectively, along with the 4 cm cutoff point used in most prior studies, had poor sensitivity and specificity in regards to earlier or increased rates of injury in a sample of 294 NCAA Division I athletes. Most recently, Brumitt et al [30,31] found no associations between preseason YBT-LQ test scores and non-contact LQ injury in male collegiate basketball players or female collegiate volleyball players. Based on our present study's findings and recent reports, we suggest that the YBT-LQ test ability as a sole indicator for injury is limited in collegiate American Football players, and that other screening tests should also be assessed.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Next, the subject reached towards one of three directions (anterior, posterior-medial and posterior-lateral) using their non-weight-bearing lower limb to slide the moveable platform. Three reach trials were performed in each direction, first standing on the uninvolved leg and then on the one involved (on the right leg and then on the left in control group) 44 . The final score was the mean value from three trials for each leg (evaluated leg was that weight-bearing).…”
Section: Methodsmentioning
confidence: 99%
“…Votes for the AFL Coaches Association award are cast by the senior coaches from both competing teams, and votes for the fairest and best player are cast by the field umpires. Further, various clubs use subjective coach ratings as a way of determining club based awards [15], and various media sources publish subjective ratings for public interest.…”
Section: Introductionmentioning
confidence: 99%